SsSm1, a Cerato-platanin family protein, is involved in the hyphal development and pathogenic process of Sclerotinia sclerotiorum. (May 2018) - Pan, Yuemin; Wei, Junjun; Yao, Chuanchun; Reng, Hengxue; Gao, Zhimou
Highlights: We discover SsSm1, a Cerato-platanin family protein in Sclerotinia sclerotiorum . SsSm1 is an novel elicitor, can trigger cell death in Nicotiana benthamiana . SsSm1 is involved in hyphal development, affects tolerances to chemical stress response. SsSm1 silenced mutants exhibit reduced pathogenicity of Sclerotinia sclerotiorum . Abstract: The filamentous fungus Sclerotinia sclerotiorum is an important plant pathogen with a worldwide distribution. It can infect a wide variety of plants, causing serious disease in many types of crops, such as rapeseed, sunflower and soybean. Sclerotinia stem rot caused by this fungus affects main crops and has led to great economic loss. Elicitors are a group of compounds that inspire the host plant to produce an immune response against invading pathogens. This study describes a protein that has high homology with the Trichoderma elicitor Sm1 and was found in the genome of S. sclerotiorum . We named this protein SsSm1. To determine whether this protein has an elicitor function like its homology protein, we constructed a heterologous expression vector for SsSm1 and expressed it in Escherichia coli . The protein of heterologous expression led to the formation of lesions in tobacco that closely resemble hypersensitive response lesions. Transient expression of the encoding gene of SsSm1 in tobacco leaves also caused hypersensitive response. Then, RNA silencing was used to identify the function of SsSm1. The hyphal growth and pathogenicity of silenced transformants were shown to be obviously lagging and branched abnormally. Transformants produced less infection cushions and deformed sclerotiorum. In addition, SsSm1 silencing caused weak tolerance to NaCl, sorbitol and SDS, and the sensitivity of mutants to carbendazim was also significantly decreased. Based on the above results, we speculate that this protein may be related to the development of hyphae, infection cushions and sclerotiorum, but the specific molecular mechanism needs to be studied further.